Effect of Tempering Temperature on the Low Temperature Impact Toughness of 42CrMo4-V Steel - Chen Sun; Pai-Xian Fu; Hong-Wei Liu; Hang-Hang Liu; Ning-Yu Du (Metals, 2018)
Effects of tempering temperature on the microstructures and low temperature impact toughness of 42CrMo4-V steel were investigated. Microstructures of 42CrMo4-V steel after tempering at 570–720 °C for 3 h were experimentally investigated using scanning electron microscopy (SEM), electron back-scattered diffraction (EBSD), transmission electron microscopy (TEM) and X-ray diffraction (XRD). The results showed that the carbide precipitation sequence of 42CrMo4-V steel is M8C7 → M3C and the absorbed energies of 42CrMo4-V steel increase greatly from 21.7 J to 132.3 J with increasing tempering temperature from 570 °C to 720 °C. The changes of impact toughness with increasing tempering temperature were attributed to the softening of matrix, the evolution of carbide precipitates and grain structures.